2021
DOI: 10.2196/29071
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Implementation and Effectiveness of the Electronic Patient-Reported Outcome Tool for Older Adults With Complex Care Needs: Mixed Methods Study

Abstract: Background Goal-oriented care is being adopted to deliver person-centered primary care to older adults with multimorbidity and complex care needs. Although this model holds promise, its implementation remains a challenge. Digital health solutions may enable processes to improve adoption; however, they require evaluation to determine feasibility and impact. Objective This study aims to evaluate the implementation and effectiveness of the electronic Patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…The total cost of the ePRO tool was CAD $79,467 (~US $63,581; CAD $1733 [~US $1386] per person); of these, the technology component accounted for 90.89% (CAD $72,234 [~US $57,794]) of the total costs. The trial reported that ePRO combined with usual multidisciplinary care did not significantly impact patient HRQoL ( P =.24) or patient activation ( P =.17) [ 10 ]. Our base case analysis showed that, compared with the standard care, the addition of the ePRO intervention was associated with higher costs (CAD $7133 [US $5707] vs. CAD $5423 [US $4338] per patient) and slightly fewer QALYs (0.42 vs. 0.45) than usual care ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The total cost of the ePRO tool was CAD $79,467 (~US $63,581; CAD $1733 [~US $1386] per person); of these, the technology component accounted for 90.89% (CAD $72,234 [~US $57,794]) of the total costs. The trial reported that ePRO combined with usual multidisciplinary care did not significantly impact patient HRQoL ( P =.24) or patient activation ( P =.17) [ 10 ]. Our base case analysis showed that, compared with the standard care, the addition of the ePRO intervention was associated with higher costs (CAD $7133 [US $5707] vs. CAD $5423 [US $4338] per patient) and slightly fewer QALYs (0.42 vs. 0.45) than usual care ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the trial, the study population for this cost-utility study was community-dwelling individuals aged 60 years or older with complex chronic conditions, defined as diagnosed with 2 or more chronic conditions and 10 or more visits to their primary health care provider within the past year. This number of visits has been identified as an indicator of complexity [ 10 ]. Chronic conditions were identified through the FHTs electronic medical records.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations